CONCEPTUAL DESIGN AS A METHODOLOGY OF HARMONIOUS FORMATION OF CLASSIC MEN’S AND WOMEN’S SUIT - Kolosnichenko, O. V.; Pashkevych, K. L.; Ostapenko , N. V.; Krotova , T. F.; Kolosnichenko , M. V. (Art and Design, 2023)
Purpose: study of the methods of harmonizing the form of pret-a-porter clothes by establishing the conceptual correspondence of the aesthetic properties of the form and its functional features in the design of classic men’s and women’s suits. Methodology. The research methodology is determined by a comprehensive study of the subject, based on the use of historical and cultural and comparative methods; methods of formal, functional and semiotic analysis were used. The paper uses art history and art-design scientific approaches. The theoretical and methodological basis of the study is based on the scientific provisions of the theory of clothing design, as well as on the scientific papers and methodological developments of specialists in the history of costume and clothing design. Results. Forming methods as a system of creative ideas and functionally expedient solutions for balancing function-aesthetics in the design-ergonomic design of an assortment of promising collections of men’s and women’s clothing, taking into account the plasticity of fabrics, have been studied. The factors influencing the material on the structural and tectonic characteristics of the formation according to the function of the classical suit have been determined. The conceptual correspondence of the harmonization of the form, its aesthetic properties and functional features has been established; the peculiarities of the means of compositional expressiveness in the development of harmonious forms of modern classical costume as a separate valuable component of clothing design have been revealed. Scientific novelty. Of the study consists in the implementation of a comprehensive study of modern classical clothing as an object and subject of conceptual design: the artistic origins of the harmonious formation of conceptual collections are revealed; the stages of its harmonious development are determined. It is noted that the value-meaning environment with reference to cultural, mental, social and other contexts becomes identifying for the conceptual suit. Practical significance. The practical significance of the study is the creation of a scientific base for the development of harmonious forms of collections of classic suits for the construction of a constructive arrangement of models of the collection of men’s and women’s assortment. The practice of applying theoretical research will help in the educational process of training fashion designers and clothing designers.